La necesidad de trascendencia: clave de la calidad educativa - Flores Quelopana, Gustavo (2010)
Education is fundamentally about humanizing rather than just teaching. In a postmodernculturalcontextofdisbelieve, nihilism, and relativism, education should assume the development of the human need to transcend as a key element for educational quality.